Surviving busy season: Using the job demands‐resources model to investigate coping mechanisms - Jefferson, Devon P.; Andiola, Lindsay M.; Hurley, Patrick J. (Contemporary Accounting Research, 2025)
Abstract Fatigue and burnout are root causes of audit quality issues and turnover. Leveraging the job demands‐resources theory, we investigate whether two mechanisms can reduce accountants' fatigue and, in turn, improve audit quality. We conduct a field study of public accountants during both normal and busy season work periods, collecting bi‐daily logs to examine whether the use of microbreaks (i.e., brief respite activities) as a job crafting mechanism and/or the receipt of supervisory support as a job resource lessen end‐of‐day fatigue. We posit and find that engaging in microbreaks is associated with reduced end‐of‐day fatigue within busy season. Similarly, we posit and find that higher levels of daily supervisory support during busy season are associated with lower end‐of‐day fatigue. However, neither of these mechanisms is associated with lower end‐of‐day fatigue during normal work periods. Our results also indicate that these two mechanisms function as complements during busy season, with either one significantly reducing end‐of‐day fatigue, but both together having an interactive effect. Further, end‐of‐day fatigue during busy season reduces sleep quality, which increases accountants' fatigue the following morning. In a follow‐up experiment, we consistently find evidence that a 1‐min microbreak reduces fatigue and that this reduction directly translates into improved error detection.